PENDAMPINGAN KOMERSIALISASI MINUMAN HERBAL BAGI PENGURUS DAERAH AISYIYAH KOTA MALANG - Wahyuni, Endang Dwi; Suprapti, Eny (Studi Kasus Inovasi Ekonomi, 2018)
Goals the activities to provide business motivation as well as assistance commercialization of herbal drinks for the Regional Board Aisyiyah Malang . Aisyiyah management already has a cooperative that can be used as a container to market their products. During this product sold in the cooperative quite a lot, among others: school uniforms, school equipment, snacks and various types of beverages. However, the products sold, there is no production of Aisyiyah citizens themselves. Therefore, it is necessary to motivate the herbal beverage business for the board and members to capture the existing business opportunities, while providing commercialization assistance.The results of direct training is practiced and sold at every bazaar event that is always held every activity conducted by Economic and Entrepreneurship Assembly, PDA Malang. Advisory activities are carried out directly whenever any complaints or obstacles are encountered, such as issues related to storage durability or expiration period, hygienic packaging, unpleasant taste, use / addition of other materials, etc.